Diversidad y abundancia de hongos Basidiomycetes según tipo de sustrato en el bosque del campus universitario - Zungarococha - facultad de ciencias biológicas - UNAP. Iquitos - Perú - Sicchar Silva, Claudia Lucia (2022)
In the present research work, the diversity and abundance of Basidiomycetes fungi were determined according to the type of substrate in the forest of the University Campus of the Faculty of Biological Sciences - Zungarococha between the months of March to July 2020, the study area was divided into 15 transects with dimensions of 4m by 100m each, the collected samples were recorded in the collection form and transported to the Mycology Laboratory of the Natural Resources Research Center (CIRNA) for taxonomic identification. A total of 2551 individuals distributed in 84 species belonging to 37 genera, 22 families and 11 orders were reported. Being Rigidoporus lineatus (22.89%) the most abundant species. The most frequent taxa were the genus Rigidoporus (35.36%), the family Meripilaceae (35.36%), the order Poliporales (49.86%). According to the substrate preference of the basidiomycetes, 71 lignicolous species, 12 foliar species and 1 terrestrial species were recorded. With respect to the diversity according to the type of substrate, the Kruskal-Wallis test was carried out, where it was recorded that there are significant differences between the medians of the groups studied (substrates), in this way affirming that it does influence the diversity of the Basidiomycetes.